Complex karyotype, older age, and reduced first‐line dose intensity determine poor survival in core binding factor acute myeloid leukemia patients with long‐term follow‐up. Issue 6 (1st April 2015) - Mosna, Federico; Papayannidis, Cristina; Martinelli, Giovanni; Di Bona, Eros; Bonalumi, Angela; Tecchio, Cristina; Candoni, Anna; Capelli, Debora; Piccin, Andrea; Forghieri, Fabio; Bigazzi, Catia; Visani, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> Approximately 40% of patients affected by core binding factor (CBF) acute myeloid leukemia (AML) ultimately die from the disease. Few prognostic markers have been identified. We reviewed 192 patients with CBF AML, treated with curative intent (age, 15–79 years) in 11 Italian institutions. Overall, 10‐year overall survival (OS), disease‐free survival (DFS), and event‐free survival were 63.9%, 54.8%, and 49.9%, respectively; patients with the t(8;21) and inv(16) chromosomal rearrangements exhibited significant differences at diagnosis. Despite similar high complete remission (CR) rate, patients with inv(16) experienced superior DFS and a high chance of achieving a second CR, often leading to prolonged OS also after relapse. We found that a complex karyotype (i.e., ≥4 cytogenetic anomalies) affected survival, even if only in univariate analysis; the KIT D816 mutation predicted worse prognosis, but only in patients with the t(8;21) rearrangement, whereas FLT3 mutations had no prognostic impact. We then observed increasingly better survival with more intense first‐line therapy, in some high‐risk patients including autologous or allogeneic hematopoietic stem cell transplantation. In multivariate analysis, age, severe thrombocytopenia, elevated lactate dehydrogenase levels, and failure to achieve CR after induction independently predicted longer OS, whereas complex karyotype predicted shorter OS only in univariate analysis. The achievement of minimal residual disease negativity predicted better OS and DFS. Long‐term survival was observed also in a minority of elderly patients who received intensive consolidation. All considered, we identified among CBF AML patients a subgroup with poorer prognosis who might benefit from more intense first‐line treatment. Am. J. Hematol. 90:515–523, 2015. © 2015 Wiley Periodicals, Inc.